THE CALCULATION OF THIN-WALLED COMPRESSED BENT METAL ELEMENTS - , В. О., Д. А. (Municipal economy of cities. Series: «Economy science», 2013)
Comparison of calculations centrally compressed thin-walled curved metal elements by methods outlined in the draft EN-N B A.2.2 and European standards EN 1993-1-3 an example of calculating the short rack with C-shaped profile.